O ensino de filosofia no ensino fundamental: revisitando o que foi estudado na última década (2001-2010) - Galves, Iracema Cerdán (2012)
This paper presents a literature review focused exclusively on academic dissertations and PhD theses, held in the period between 2001 and 2010, on Philosophy in Elementary Education. We analyzed 14 of them, in order to verify, according to their authors, the perceived advantages of offering this subject to children initiating the school process. The results showed that the study of philosophy is seen as important for the development of cognitive skills, since it encourages creativity and criticality and contributes both to the authenticity and the development of reasoning and the search for true answers. This discipline is also seen as allowing the construction of attitudes and behaviors necessary to democratic citizenship. Although the learning of philosophy cannot be considered the only way to achieve these goals, in globalized societies, where neo-liberal values prevail, acquaintance with it becomes a strong and desirable option to offset the negative influence of this economy on people s modes of feeling, thinking and acting